Performing the Canadian West: Chuckwagons, Cowgirls, and New Westerns. (February 2016) - Polić, Vanja
This article's analysis will revolve around the contemporary literary reconfigurations of the myth of the old West with special attention to the Wild West as a performed space and a performed narrative. Attention will be paid to the reconfiguration of the myth by focusing, in turn, on chuckwagon races as "a synecdoche of the West" (van Herk) and their carnivalesque quality; the myth versus reality debate always accompanying the myth of the Wild West as well as the narrativization of the West; female characters who claim the spotlight of the new West; the ironic treatment of the traditional cowboy icon; and the front stage–back stage relations that contribute to the Wild West's performativity and the ultimate survival in the postmodern world. The strategies of the myth's dis- and re-membering as represented in two texts by Aritha van Herk—the short story "Leading the Parade" and the performance piece "Shooting a Saskatoon (Whatever Happened to the Marlboro Man?)"—will be examined to reveal an emergent new Canadian West.